Inner Conflict and Moral Consciousness in Qamar al-Zamān: A Freudian Psychoanalytic Interpretation - Azzamsyah, Muhammad Raihan; Sa'adah, Rd. Siti (UIN Syarif Hidayatullah Jakarta, 2025)
This study analyzes the dynamics of the personality structure of the characters in the tale